Stevens Johnson Syndrome: A Case Report - Peter Nugraha Soekmadji; Theresia Monica Rahardjo; Riza Chandra Luthfy; Stevani Abigail; Nadya Naurah Adrina Suardi; Risha Diranti Ananda Putri (Medical Clinical Update, 2023)
Steven Johnson Syndrome is an allergic reaction and in severe condition can be life-threatening. This condition can result in systemic symptoms and sometimes need intensive management. This case report aimed to present a diagnosis and treatment of a Steven Johnson Syndrome in clinic